Characterization of Host lncRNAs in Response to Vibrio splendidus Infection and Function as Efficient miRNA Sponges in Sea Cucumber - Zhang, Siyuan; Shao, Yina; Li, Chenghua (Frontiers in Immunology, 2021)
Long non-coding RNAs (lncRNAs) have been reported to play critical roles during pathogen infection and innate immune response in mammals. Such observation inspired us to explore the expression profiles and functions of lncRNAs in invertebrates upon bacterial infection. Here, the lncRNAs of sea cucumber (Apostichopus japonicus) involved in Vibrio splendidus infection were characterized. RNA-seq obtained 2897 differentially expressed lncRNAs from Vibrio splendidus infected coelomocytes of sea cucumbers. The potential functions of the significant differentially expressed lncRNAs were related to immunity and metabolic process based on the gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Moreover, we identify a lncRNA (XLOC_028509), which is downregulated with Vibrio splendidus challenged, further study indicated that XLOC_028509 adsorb miR-2008 and miR-31 as competing endogenous RNAs (ceRNAs) through base complementarity, which in turn decreased the amount of miRNAs (microRNAs) bound to the 3’UTRs (untranslated regions) of mRNAs to reduce their inhibition of target gene translation. These data demonstrated that the lncRNAs of invertebrates might be important regulators in pathogen-host interactions by sponging miRNAs.